Stimulation of transcription on chromatin by polar organic compounds. - Strätling, W H (1976)
Polar organic compounds, including DMSO, increase RNA synthesis on isolated chromatin by E. coli RNA polymerase and RNA polymerase II from calf thymus. Transcription is stimulated on chromatin from Friend-virus-infected erythroleukemia cells and from various other sources. Using procedures which inhibit specifically the formation of a stable initiation complex, it is shown that the stimulation does not result from an increase in initiation of both E. coli and the eukaryotic RNA polymerase. After separation of chromatin into template active and inactive fractions, DMSO increases RNA synthesis by a factor of about 1.5 using the template inactive fraction, while stimulation of transcription on the template active portion is lower (factor of 1.2). It is suggested that the effect on RNA synthesis is mediated by a weakening of the apolar interactions between histones in chromatin subunits, releasing transcription partially from the constraints imposed by histones.